Former NICU Families Describe Gaps in Family-Centered Care. (October 2020) - Sigurdson, Krista; Profit, Jochen; Dhurjati, Ravi; Morton, Christine; Scala, Melissa; Vernon, Lelis; Randolph, Ashley; Phan, Jessica T.; Franck, Linda S.
Care and outcomes of infants admitted to neonatal intensive care vary and differences in family-centered care may contribute. The objective of this study was to understand families' experiences of neonatal care within a framework of family-centered care. We conducted focus groups and interviews with 18 family members whose infants were cared for in California neonatal intensive care units (NICUs) using a grounded theory approach and centering the accounts of families of color and/or of low socioeconomic status. Families identified the following challenges that indicated a gap in mutual trust and power sharing: conflict with or lack of knowledge about social work; staff judgment of, or unwillingness to address barriers to family presence at bedside; need for nurse continuity and meaningful relationship with nurses and inconsistent access to translation services. These unmet needs for partnership in care or support were particularly experienced by parents of color or of low socioeconomic status.